Bubble size distribution and stability of CO2 microbubbles for enhanced oil recovery: effect of polymer, surfactant and salt concentrations. Issue 5 (19th April 2023) - Nguyen Hai Le, Nam; Sugai, Yuichi; Nguele, Ronald; Sreu, Tola
Abstract: Fluids incorporating carbon dioxide (CO2 ) microbubbles have been utilized to promote enhanced oil recovery from hydrocarbon reservoirs. The performance of such fluids in porous media is greatly affected by both the bubble size and stability. On this basis, the present study evaluated the effects of varying the concentrations of a xanthan gum (XG) polymer, a surfactant (sodium dodecyl sulfate: SDS) and sodium chloride (NaCl) on both the stability and bubble size distribution (BSD) of CO2 microbubbles. CO2 microbubble dispersions were prepared using a high-speed homogenizer in conjunction with the diffusion of gaseous CO2 through aqueous solutions. The stability of each dispersion was ascertained using a drainage test, while the BSD was determined by optical microscopy and fitted to either normal, log-normal or Weibull functions. The results showed that a Weibull distribution gave the most accurate fit for all experimental data. Increases in either the SDS or XG polymer concentration were found to decrease the microbubble size. However, these same changes increased the microbubble stability as a consequence of structural enhancement. The addition of NaCl up to a concentration of 10 g/L (10 g/1000g) decreased the average bubble size by approximately 2.7%. Stability was also reduced as the NaCl concentration was increased because of the gravitational effect and coalescence. Graphical Abstract: UF0001